VO2 Responses to Running Speeds Above Intermittent Critical Speed - de Aguiar, R. A.; Turnes, T.; de Oliveira Cruz, R. S.; Caputo, F. (International Journal of Sports Medicine, 2012)
The aim of this study was to examine whether intermittent critical speed (ICS) is the threshold velocity above which intermittent exercise leads to the attainment of VO2max. After an incremental test, 7 active male subjects (49.7±3.74 mL.min − 1.kg − 1) performed 3 intermittent exercises until exhaustion at 100%, 110%, 120% of the velocity associated with VO2max to determine ICS. On 4 occasions, the subjects performed intermittent exercise tests until exhaustion at the velocity corresponding to 105% (IE105) and 110% (IE110) of ICS, and at a speed that was initially set at 125%ICS but which then decreased to 105%ICS (IE125–105) in one instance and to 110%ICS (IE125–110) in another. The intermittent exercises consisted of repeated 30-s runs alternated with 15-s passive rest intervals. At IE125–105, peak VO2 was not different from VO2max but decreased significantly after the change of speed to 105%ICS. During IE110, peak VO2 value reached VO2max and also during the higher speed at IE125–110, but did not change when the speed was lowered. These results demonstrated that during intermittent exercise just above ICS (105%) VO2max was not elicited, suggesting that ICS might not be the threshold speed above which VO2max can be reached.
Keywords: intermittent exercise; critical speed; VO2max; running